Erratum to High entropy steel processed through mechanical alloying and spark plasma sintering Alloying behaviour, thermal stability and mechanical properties - Jain, Harsh; Shadangi, Yagnesh; Chakravarty, Dibyendu; Dubey, Ashutosh Kumar; Close Mukhopadhyay, N.K. (Elsevier Ltd, 2022)
The temperature effect on forming gradient structure in an Al–Si alloy during surface severe deformation is studied in this report. The intermediate temperature (473 K) produces the steepest gradient structure by an anomalous hardening on the top layer compared to lower (300 K) and higher temperature (673 K) counterparts. Our analysis shows profuse aluminum oxide particles in the top layer of the gradient structure under 473 K lead to anomalous hardening by oxide-dispersion strengthening. The counterintuitive enhancement of strengthening at the intermediate temperature is explained by the dynamic interplay between thermal-driven, mechanical- aided oxidation and the wear-induced loss of surface materials as a function of temperature, which yields a critical processing temperature to achieve the steepest gradient structure
This paper is submitted by the author of IIT (BHU), Varanasi, India
Keywords: Erratum; High entropy steel processed; Alloying and spark plasma; Thermal stability; Mechanical properties